Assessing the impact of toll gate construction on land cover alterations with google earth engine - Rendy Akbar; Softy Nuzzela; Andi M. Ahsan Mukhlis (Journal of Infrastructure Planning and Engineering, 2025)
In recent years, the Indonesian government has been aggressively pursuing toll road development. Infrastructure projects such as toll roads are known to stimulate economic growth and enhance the mobility of goods and people. This economic growth and increased mobility, in turn, accelerate the process of urbanization. Areas surrounding toll roads, particularly near access points and interchanges, often undergo land use conversion towards functions with higher economic value. Consequently, the presence of a toll road generates a multiplier effect on the surrounding region, encompassing both positive and negative impacts. The Trans-Java Toll Road, a major project connecting the western and eastern ends of Java Island, has been under development for a considerable period. Construction began in 1984, with the connection to Surabaya completed in 2018. Currently, the toll road extends to Probolinggo and is planned to reach Banyuwangi by 2025, spanning a total length of 1,167 km. This study aims to investigate the land cover changes resulting from the construction of the Trans-Java Toll Road, from Merak in the west to Probolinggo in the east of Java. This research employs a quantitative approach, utilizing spatial analysis and descriptive statistics within the Google Earth Engine platform to identify and analyze these land cover changes. This study reveals significant and consistent land cover transformations across the seven analyzed interchanges. Key findings from 1990 to 2020 indicate a universal increase in built-up areas, most substantially observed at the Surabaya interchange, which experienced a 17,681.09 Ha expansion of built-up land. This growth largely occurred at the expense of green areas, which decreased by 15,898.91 Ha in Surabaya and 8,102.97 Ha in Semarang. The Tangerang interchange also showed significant urbanization, with a 3,596.00 Ha increase in built-up land. These findings can serve as a crucial reference for anticipating and mitigating the potential negative consequences of future toll road projects, particularly as the government intensifies infrastructure development in regions outside of Java.